Womens perceptions of the reasons of physical and sexual abuse after requesting safe sex in a sexual relationship to prevent HIV and AIDS - Ngonje, Cathrine (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.